Celiac Disease and Migraine Headaches: Current Knowledge and Future Directions - Wojciechowska, Klara; Ślósarz, Tymoteusz; Turek, Monika; Piątkowska, Karolina; Walęcik-Kot, Weronika (Journal of Education, Health and Sport, 2023)
Background: Migraine headaches and celiac disease are widespread problems affecting millions of patients worldwide. Celiac disease is an autoimmune disease in which the consumption of gluten leads to the development of an abnormal immune response in the intestines and the atrophy of intestinal villi. The most characteristic clinical symptoms of celiac disease are gastrointestinal symptoms. Nevertheless, manifestations of the nervous system, including migraines, are also sometimes noted. A gluten-free diet is the only effective therapeutic approach for patients with celiac disease. It reduces symptoms and halts the progression of the disease. Neurological symptoms, including migraines, are frequent extraintestinal manifestations. In this study we aim to elaborate on current knowledge concerning both coexisting of migraines and celiac disease as well as effect of gluten free diet on headaches in patients with celiac disease, gluten intolerance and healthy individuals Results: Headaches, especially migraines, are more common in patients suffering from celiac disease. Numerous studies indicate that a gluten-free diet may help in the treatment of headaches and is also an effective way to stop the progression of celiac disease. Conclusion: Migraine headaches are quite common in patients with celiac disease, and a gluten-free diet may help alleviate them. The findings suggest the need for increased awareness of the co-occurrence of these two conditions. A gluten-free diet is the only effective treatment for celiac disease and can stop progression of the disease. Further research is needed to determine the potential benefits of such a diet in patients with gluten intolerance or healthy individuals.